STUDI HUKUM POSITIF DAN HUKUM ISLAM TERHADAP EKSPLOITASI TUBUH WANITA MELALUI LIVE STREAMING DI MEDIA SOSIAL - Fianto, M. Alif; Syamsuri, Syamsuri (Universitas Nurul Jadid, 2023)
It cannot be denied that pornography is something that can bring someone closer to adultery. It has the ability to trigger real passion. The results of several surveys conducted to date increasingly confirm that pornography is indeed a significant trigger for lust. Therefore, as such, pornography in all its forms is forbidden (haram) in Islam. The prohibition of pornography has the same position as the prohibition of other behaviors that are an introduction and trigger for adultery, such as tabarruj (deliberately exposing one's face, beauty, clothing, jewelry and speech), being alone with the opposite sex (khalwat), songs obscene songs, and the like. In this context, jarimah refers to actions that are prohibited by Islamic law and are threatened with had punishment (predetermined punishment). The perpetrator deliberately distributes pornographic content so that viewers can enjoy it and the perpetrator makes money from this content. According to Article 4 paragraph (1) of the pornography law, all criminal acts of pornography are considered acts committed intentionally (dolus). Even though it does not directly mention the element of intention, pornographic acts carried out on the Mango Live application can be categorized as acts carried out intentionally because the perpetrator has certain motives and goals in carrying out these actions. However, Article 27 paragraph (1) of the ITE Law clearly states that the elements must be present in the formulation, so that acts of pornography or violations of decency are included in the category of violations.